FERTILIZACIÓN EDÁFICA EN EL CULTIVO DE CACAO (Theobroma cacao L.) Y SU INCIDENCIA EN LA FRUCTIFICACIÓN - ROMERO PEREZ, ANGEL FRANCISCO (2023)
As is generally known, cocoa (Theobroma cacao L.) is one of the most economically important traditional crops in Ecuador, it is cultivated by countless families immersed in its production and marketing. A transcendental issue in this crop is nutrition, which is very important for the crop to develop physiologically and grow optimally, obtaining the expected production levels. In this research work, it was proposed to evaluate the efficiency of different chemical fertilizers used in soil fertilization of cocoa crops and their impact on the performance of the final product, all with the aim of verifying which of these products most closely resembles the requirements. nutritional requirements demanded by this crop to express its maximum genetic potential. The research developed was experimental (completely randomized blocks) where the productive behavior of the CCN-51 cocoa crop was recorded in response to the application of three commercial fertilizers (T1 Ferticacao, T2 Dr. Cacao, T3 YaraMila Complex) and a witness (T0). The effect of fertilizers on the productive stage of the crop was quantitatively evaluated, for which the following variables were presented to be measured: flowering index, fruiting index and incidence of Cherrelle Wilt. Based on the results obtained, it was established that the treatment with the best results in the flowering index was T2 (DrCacao) with an average of 1.66. Regarding the fruiting index, the treatment that showed the best results was T3 (Yaramila Complex) with an average of 1.63. And, finally, in the Cherrelle Wilt index, it was found that the treatment with the highest incidence was T0 (Control) with an average of 1.71.